2014
DOI: 10.4269/ajtmh.13-0248
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Artemisinin-Based Combination Treatments of Uncomplicated Falciparum Malaria in Under-Five-Year-Old Nigerian Children

Abstract: The efficacy of 3-day regimens of artemether-lumefantrine and artesunate-amodiaquine were evaluated in 747 children < 5 years of age with uncomplicated malaria from six geographical areas of Nigeria. Fever clearance was significantly faster (P = 0.006) and the proportion of children with parasitemia 1 day after treatment began was significantly lower (P = 0.016) in artesunate-amodiaquine—compared with artemether-lumefantrine-treated children. Parasite clearance times were similar with both treatments. Overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 39 publications
(60 reference statements)
6
44
1
Order By: Relevance
“…This is higher than the 25.5% prevalence documented by Oguche and colleagues in a study in Nigerian children published in 2014 [20]. Their slightly lower prevalence might be because they reported the national average from different regions rather than a single region done by this study.…”
Section: Discussioncontrasting
confidence: 53%
“…This is higher than the 25.5% prevalence documented by Oguche and colleagues in a study in Nigerian children published in 2014 [20]. Their slightly lower prevalence might be because they reported the national average from different regions rather than a single region done by this study.…”
Section: Discussioncontrasting
confidence: 53%
“…In Nigeria, studies indicate that malaria transmission is still high 21,34 , with recent studies from regions in Nigeria reporting high mutations in genes that modulate response to nonartemisinin drugs by P. falciparum [35][36][37] . Conversely, other studies have reported high in-vivo response after ACTs with parasitemia half-life <5 hours, and 42-day cure rates >90% 38 . However, few studies elsewhere have recently evaluated the WHO benchmarks for artemisinin resistance using RSA value and K13 gene polymorphism 17,20 .…”
Section: Discussionmentioning
confidence: 84%
“…The later study was conducted from 2009 to 2014 in malarious children ≤10 years old in Ibadan. The details of the efficacy and gametocyte carriage study have been reported elsewhere [8,9]. The study profile is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The day of presentation was regarded as day zero. Patients were treated with artemether-lumefantrine (AL) or artesunate-amodiaquine (AA) co-formulated for 3 days (days 0-2) as previously described [9]. In the initial study, follow-up was done daily on days 1-3 and on days 7, 14, 21, and 28, and this was extended to days 35 and 42 in the later study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation